Distributed Cloud Computing and Mobile Cloud Computing: A Review - Nashma Taha Muhammed; Subhi R. M. Zeebaree; Zryan Najat Rashid (QALAAI ZANIST JOURNAL, 2022)
Cloud-based data storage has grown in popularity due to its flexibility and concerns about security and confidentiality. In computer science, cloud computing is a relatively new concept. Users are using fewer resources while increasing their reliance on cloud resources. Cloud computing, mobile computing, and wireless networks are combined in Mobile Cloud Computing (MCC). On the other hand, Mobiles provide vast computational resources to mobile consumers due to their capabilities. On the other hand, cloud computing refers to data centers that are accessible via the Internet to a large number of people. The purpose of this paper is to provide an overview of cloud computing and mobile cloud computing. The study covers delivery and deployment models of cloud computing and the main features of mobile cloud computing.